HUBUNGAN ANTARA KELEBIHAN BERAT BADAN DENGAN STATUS HEMOGLOBIN PADA SISWI SEKOLAH MENENGAH ATAS ATAU SEDERAJAT DI JAKARTA - Indriantika, Fitria; Soekatri, Moesijanti (GIZI INDONESIA, 2009)
THE RELATIONSHIP BETWEEN OVERWEIGHT AND HAEMOOGLOBIN (Hb) LEVEL AMONG HIGH SCHOOL FEMALE STUDENTS IN JAKARTAAnemia is one of the four nutrion problem in Indonesia and most of anemia is closely associated toiron deficiency called iron deficiency anemia (IDA). Study in USA among adolesents showed that theprevalent of IDA is higher in overweight (9.1%) than normal weight (3.1%). Another study inSwitzerland among teenage female students showed that the fat deposit in adipose tissue maydecrease iron absoption. The aim of this study is to know the relationship between overweight andhaemoglobin (Hb) level using cross sectional.The female subjects were selected purposively withcriteria as they were overweight (BMI >= 25)and registered as female students at SMAN 4, SMAN 25and SMKN 38 in Jakarta. The overweight status were determined using Body Mass Index and finally35 female students were filling the criteria and willing to participate. The correlation Person test wasused to see the realtionship between overweight and Hb level.The results showed that most of thesubjects (82.9%) were categorized as obese and most of them were in the aged of 16 and 17 years(37.1% each). About 80% of the students had a normal haemoglobin level, More than half (88.6%) hada normal mentruation period. However, the Hb level less than normal (<12 gr/dL) were mostly found inobese subjects (57%) rather than overweight(43%). In Hb level, 80%of them had a normalhaemoblobon level. The correlation test showed that there is no significant relationship betweenoverweight and Hb level (p=0.149, r=0.181). In needs to do the similar study with the larger group andusing iron cpncentration test in blood.Keywords: overweight, Hb status, high school female student